Modern management - Certo, Samuel C. (Pearson/Prentice Hall, 2006)
This book provides a comprehensive, flexible approach to the basic skills of business management with an emphasis on skills and applications. It presents traditional concepts, important contemporary issues, and timeless insights into applying management know-howndash;all toward the goal of achieving organizational success. Built around the concept of ldquo;Core Plusrdquo; - a core of chapters covered in most courses, surrounded by a rich selection of optional chapters - enabling flexibility in the way the text is used.Management History, Operations Management, Information Technology in Management, and Creativity and Innovation in Management.For managers at all levels.